Comparative efficacy of benthic biotic indices in assessing the Ecological Quality Status (EcoQS) of the stressed Ulhas estuary, India. Issue 1 (15th July 2017) - Mulik, Jyoti; Sukumaran, Soniya; Srinivas, Tatiparthi; Vijapure, Tejal
Abstract: Ecostatus of Ulhas estuary, one of the most polluted estuaries along the industrialized and urbanized northwest coast of India, was evaluated by six widely accepted benthic indices viz. H ′(log2 ), AMBI, M-AMBI, BENTIX, BOPA and BO2A to test their efficiency in a tropical setting. The mesohaline zone, which presented eutrophic conditions, was classified as 'bad' by all indices due to the azoic status. Despite significant correlations obtained between indices, there were discrepancies in the accurate level of EcoQS assigned to each station. AMBI was observed to be most efficient in indicating a clear spatial variability from a 'poor' to 'bad' ecological quality status in the middle and upstream zones to an improved status in the downstream region. Limitations of all indices are discussed in light of their suitability for assessing the estuarine environmental condition. The present results could provide a fillip to environmental improvement initiatives currently being undertaken in the estuary. Highlights: Six biotic indices were used to assess the EcoQS of the Ulhas estuary. All indices correctly classified the eutrophic defaunated mesohaline zone as 'bad'. AMBI performed satisfactorily in evaluating the EcoQS of all the stations. Results provide model for future ecological appraisal of tropical estuaries.